HLA-DR3 restricted environmental epitopes from the bacterium Clostridium tetani have T cell cross-reactivity to the SLE-related autoantigen SmD - Zhao, Zhenhuan; Anderson, Ashley N.; Kannapell, Carol C.; Kwok, William W.; Gaskin, Felicia; Fu, Shu Man (Frontiers in Immunology, 2022)
HLA-DR3 (DR3) is one of the dominant HLA-DR alleles associated with systemic lupus erythematosus (SLE) susceptibility. Our previous studies showed multiple intramolecular DR3 restricted T cell epitopes in the Smith D (SmD) protein, from which we generated a non-homologous, bacterial epitope mimics library. From this library we identified ABC247-261 Mimic as one new DR3 restricted bacterial T cell epitope from the ABC transporter ATP-binding protein in Clostridium tetani. It activated and induced autoreactive SmD66-80-specific T cells and induced autoantibodies to lupus-related autoantigens in vivo. Compared to healthy donors, SLE patients have a greater percentage of cross-reactive T cells to ABC247-261 Mimic and SmD66-80. In addition, we analyzed the ability of single DR3 restricted Tetanus toxoid (TT) T cell epitopes to induce autoimmune T cells. We found that the immunodominant TT epitope TT826-845 stimulated SmD66-80 reactive T cells but failed to induce persistent anti-SmD autoantibodies compared to the ABC247-261 Mimic. Thus, exposure to the ABC247-261 Mimic epitope may contribute to autoimmunity in susceptible DR3 individuals.